Stakeholder perceptions and scientific evidence linking wildfire mitigation treatments to societal outcomes. (15th October 2019) - Roberts, Ryan M.; Jones, Kelly W.; Duke, Esther; Shinbrot, Xoco; Harper, Erin E.; Fons, Erin; Cheng, Antony S.; Wolk, Brett H.
Abstract: A number of watershed partnerships have emerged in the western US to address the impacts of wildfire through investing in wildfire mitigation activities. To motivate collective action and design effective risk mitigation programs, these stakeholders draw on evidence linking wildfire mitigation to outcomes of interest. To advance knowledge in this area, we 1) assessed the strength of existing scientific evidence linking wildfire mitigation treatments with societal outcomes and 2) measured the importance of this evidence to watershed partnerships in the western US. To address objective one, we created a systematic evidence map to identify the most common wildfire mitigation treatment and societal outcome relationships reported. From the more than 100 studies examined, we found that the most commonly studied linkages were related to the impacts of thinning on infrastructure and timber. To answer objective two, we surveyed 38 professionals affiliated with organizations involved in eight watershed partnerships in the western US. We asked about the relative importance and strength of evidence linking wildfire treatments to societal outcomes for their watershed partnership, and used this information to create an importance-strength analysis and gap analysis. We found that most linkages were considered important to these organizations, and that the biggest gap identified was for evidence linking mulching to water quality or quantity outcomes. Forest and wildfire specialists perceived a larger need for additional evidence generation than other professional groups. Jointly, the results from this study point to areas of evidence generation important for watershed partnerships and other organizations involved in wildfire mitigation, and suggest a need to more thoroughly disseminate information about existing evidence to this new group of stakeholders investing in wildfire risk mitigation. Highlights: A few treatment-outcome linkages are studied more extensively than others. These linkages suggest positive societal outcomes from wildfire treatments. These same relationships are viewed as highly important by decision makers. Most treatment-outcome relationships have few published studies. Wildfire specialists perceive a large need for additional study on many linkages.